Effect of vitamin D on Helicobacter pylori infection and eradication: A meta‐analysis. Issue 5 (14th August 2019) - Yang, Liping; He, Xinjue; Li, Lan; Lu, Chao
Abstract: Background: Various studies reported the relationship between Helicobacter pylori (H pylori) and vitamin D, but there is some controversy around that. This study aimed to conduct a meta‐analysis to clarify the relationship between vitamin D and H pylori infection, and vitamin D and H pylori eradication. Methods: Articles published until June 1, 2019, in the PubMed, MEDLINE, and EMBASE databases with English‐language medical studies were searched. According to the inclusion criteria, relevant statistical data were extracted to Microsoft Excel and analyzed by STATA15.1. Results: Ten articles were finally included. It was demonstrated that average 25(OH)D level in H pylori ‐positive patients was lower than H pylori ‐negative (SMD = −0.53 ng/mL, 95% CI = (−0.91, −0.16 ng/mL)). For H pylori eradication individuals, the result showed that average 25(OH)D level in H pylori successful eradication individuals was higher than unsuccessful (SMD = 1.31 ng/mL, 95% CI = [0.60, 2.02 ng/mL]). In addition, individuals with vitamin D deficiency had lower H pylori eradicate rate (OR = 0.09, 95% CI = [0.02, 0.41]). Sensitivity analysis showed that the meta‐analysis results were stable and reliable. Conclusions: Vitamin D was a protective factor to H pylori infection. Moreover, vitamin D can improve the success rate of H pylori eradication.